Airglow photometer observations and inter-relations between auroral activity and other upper atmosphere phenomena observed at Sanae, Antarctica, 1964 - Robertson, G. T.(Guy Trevor); South African National Antarctic Expedition5th1964 (Stellenbosch : Stellenbosch University, 2012)
Based on scientific observations carried out by the author during the 5th South African National Antarctic Expedition.